Gobierno electrónico y su influencia en la gestión patrimonial de la corte superior de justicia de Loreto, 2023 - Zulueta Yovanini, Katty Alexandra (2025)
This research was developed with the objective of analyzing the influence of electronic government on the asset management of the Superior Court of Justice of Loreto, 2023. Using a basic type methodology, non experimental design and descriptive level, where the sample consisted of 50 employees. of the administrative area, to which they applied a questionnaire which the results were favorable, since the Pearson graduation test was applied which showed that there is a relationship between the variables with 0.761, likewise, the significance value came out less than 0.005 demonstrating that electronic government does have significant evidence in asset management, therefore it is concluded that there is a relationship between the variables that is direct, positive and significant, deducing that as long as electronic government is developed adequately, management patrimonial will be much more efficient, allowing the achievement of objectives and optimization of the resources and assets of the institution.